KETAHANAN PANGAN DAN SIKLUS BERAS: CATATAN LAPANGAN DI DUA DESA - Faturochman Faturochman (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
Among Indonesians, food security is simply defined as rice availability. Most of Indonesians eat rice, but they cannot produce it sufficiently. While agriculture is the main sector of employment where more than 50% people absorbed and mostly they work to produce rice, Indonesia is also number one as rice importing country. It can be worse than dependent on imported rice when farmers have not stored their own harvested rice. This study shows that farmers sold rice directly from the field during the harvesting time. They were more likely to have money rather than rice that would be bought daily or weekly from markets or shops. Here, the main problem of food security appeared since they were dependent on rice markets. This article focuses on the dynamic of local rice cycle related to social, political and economic problems. The issues are discussed based on household and community data in two areas of Java. Among Indonesians, food security is simply defined as rice availability. Most of Indonesians eat rice, but they cannot produce it sufficiently. While agriculture is the main sector of employment where more than 50% people absorbed and mostly they work to produce rice, Indonesia is also number one as rice importing country. It can be worse than dependent on imported rice when farmers have not stored their own harvested rice. This study shows that farmers sold rice directly from the field during the harvesting time. They were more likely to have money rather than rice that would be bought daily or weekly from markets or shops. Here, the main problem of food security appeared since they were dependent on rice markets. This article focuses on the dynamic of local rice cycle related to social, political and economic problems. The issues are discussed based on household and community data in two areas of Java.